2017
DOI: 10.1038/srep40865
|View full text |Cite
|
Sign up to set email alerts
|

Release activity-dependent control of vesicle endocytosis by the synaptic adhesion molecule N-cadherin

Abstract: At synapses in the mammalian brain, continuous information transfer requires the long-term maintenance of homeostatic coupling between exo- and endocytosis of synaptic vesicles. Because classical endocytosis is orders of magnitude slower than the millisecond-range exocytosis of vesicles, high frequency vesicle fusion could potentially compromise structural stability of synapses. However, the molecular mechanisms mediating the tight coupling of exo- and endocytosis are largely unknown. Here, we investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 50 publications
1
37
0
Order By: Relevance
“…First CAR vectors contained only a CD3ζ‐chain domain, whereas the second generation (2G) and 3G have been developed using or combining co‐stimulatory domains such as CD28, 4‐1BB (CD137) and/or OX40 (CD134) . It is known that CD28 supports stronger T cell expansion and enhanced tumor eradication whereas activity of 4‐1BB is linked to longer persistence and reduced risk of relapse . Combining two co‐stimulatory domains in a 3G CAR vector has the potential to combine both benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First CAR vectors contained only a CD3ζ‐chain domain, whereas the second generation (2G) and 3G have been developed using or combining co‐stimulatory domains such as CD28, 4‐1BB (CD137) and/or OX40 (CD134) . It is known that CD28 supports stronger T cell expansion and enhanced tumor eradication whereas activity of 4‐1BB is linked to longer persistence and reduced risk of relapse . Combining two co‐stimulatory domains in a 3G CAR vector has the potential to combine both benefits.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 It is known that CD28 supports stronger T cell expansion and enhanced tumor eradication whereas activity of 4-1BB is linked to longer persistence and reduced risk of relapse. 45 Combining two co-stimulatory domains in a 3G CAR vector has the potential to combine both benefits. Ramos et al examined the simultaneous infusion of 2G (CD28) and 3G (CD28/4-1BB) CD19-specific CART cells into patients and demonstrated that 3G CART cells had superior expansion and persistence properties.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary antibodies were: Alexa488 goat anti‐chicken; Alexa555 goat anti‐rabbit, Alexa 555 goat anti‐mouse, Alexa647 goat anti‐mouse (all from Invitrogen, Carlsbad, CA). Transfection with EGFP plasmid was performed as described previously (van Stegen, Dagar, & Gottmann, ). Fluorescence imaging was done as described previously (Nieweg et al, ; van Stegen et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Transfection with EGFP plasmid was performed as described previously (van Stegen, Dagar, & Gottmann, ). Fluorescence imaging was done as described previously (Nieweg et al, ; van Stegen et al, ). To estimate the density of MAP2 immunostained dendrites, a line‐scan analysis was performed (using ImageJ), in which the number of dendrites crossing randomly chosen lines of defined length was counted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation